Langkah Nyata Menuju Generasi Cerdas dengan Meningkatkan Minat Belajar Anak Melalui Kegiatan Bimbingan Belajar Gratis - Titin Kempa; Jems Sopacua; Miranda Y. Kuasapy; Johan Silalebit (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Education is the main key in building an intelligent and competitive generation. However, in remote areas such as Werwaru Village, Southwest Maluku, the challenges in education are quite significant, especially in increasing children's interest in learning. Gaps in facilities, lack of motivation, and limited resources are the main obstacles to their academic development. This research aims to explore the role of free tutoring activities carried out by KKN students at Pattimura University PSDKU MBD in increasing children's interest in learning in Werwaru Village. This program is carried out for 30 days with a frequency of three times a week and involves various interactive and creative learning methods, such as group learning, personal approaches, and educational games. The research results showed an increase in children's motivation and enthusiasm for learning, which was reflected in improvements in understanding of subject matter and increased student test scores. However, challenges related to program sustainability remain a major concern, especially after KKN students complete their assignments. This research suggests the need for partnerships with local institutions to ensure this program can continue to run and have a positive impact on future generations.